(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2024)
This research paper explores the characteristics, challenges, and professional development needs of novice English language teachers, with a focus on their growth trajectory and the support required for their professional development. It discusses the unique experiences of novice teachers, such as their high enthusiasm, receptiveness to feedback, and the need for validation from experienced colleagues. Key challenges faced by novice teachers include classroom management, adapting to diverse student needs, and balancing multiple responsibilities. The paper emphasizes the role of effective induction programs, tailored professional development, and mentoring relationships as critical support mechanisms for novice teachers. Additionally, the study delves into the context of Continuing Professional Development (CPD) in Uzbekistan, highlighting the historical and structural challenges faced by English teachers and the impact of programs like the DUET initiative.